Characterization of claustral neurons by comparative gene expression profiling and dye-injection analyses - Watakabe, Akiya; Ohsawa, Sonoko; Ichinohe, Noritaka; Rockland, Kathleen S.; Yamamori, Tetsuo (Frontiers in Systems Neuroscience, 2014)
The identity of the claustrum as a part of cerebral cortex, and in particular of the adjacent insular cortex, has been investigated by connectivity features and patterns of gene expression. In the present paper, we mapped the cortical and claustral expression of several cortical genes in rodent and macaque monkey brains (nurr1, latexin, cux2, and netrinG2) to further assess shared features between cortex and claustrum. In mice, these genes were densely expressed in the claustrum, but very sparsely in the cortex and not present in the striatum. To test whether the cortical vs. claustral cell types can be distinguished by co-expression of these genes, we performed a panel of double ISH in mouse and macaque brain. NetrinG2 and nurr1 genes were co-expressed across entire cortex and claustrum, but cux2 and nurr1 were co-expressed only in the insular cortex and claustrum. Latexin was expressed, in the macaque, only in the claustrum. The nurr1+ claustral neurons expressed VGluT1, a marker for cortical glutamatergic cells and send cortical projections. Taken together, our data suggest a partial commonality between claustral neurons and a subtype of cortical neurons in the monkey brain. Moreover, in the embryonic (E110) macaque brain, many nurr1+ neurons were scattered in the white matter between the claustrum and the insular cortex, possibly representing their migratory history. In a second set of experiments, we injected Lucifer Yellow intracellularly in mouse and rat slices to investigate whether dendrites of insular and claustral neurons can cross the border of the two brain regions. Dendrites of claustral neurons did not invade the overlying insular territory. In summary, gene expression profile of the claustrum is similar to that of the neocortex, in both rodent and macaque brains, but with modifications in density of expression and cellular co-localization of specific genes.